Obesity and labor market outcomes: evidence from the British NCDS - Maarten Lindeboom; Petter Lundborg; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2009)
We study the effect of obesity on wages and employment, using data from the British NCDS. The results show a significant negative association between obesity and labor market outcomes even after controlling for a rich set of demographic, socioeconomic, environmental and behavioral variables. After instrumenting with parental obesity the associations are no longer significant. We show that the intergenerational correlation in obesity is mainly due to genetic variation. However, the instruments do not always pass the overidentification tests and are sometimes weak. We are therefore somewhat sceptical about using parental obesity as an instrument.
urn:nbn:de:101:1-20090403122
Keywords: I10; J10; 330; Obesity; wages; employment; labor; endogeneity; Gesundheitsrisiko; Lohn; Arbeitsverhältnis; Großbritannien